1971
DOI: 10.1002/aja.1001320204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bile and pancreatic secretions on the size of the intestinal villi in the rat

Abstract: Along the rat small intestine, the size of the villi gradually decreases from a maximum in the duodenum to less than half of this size in the terminal ileum. In previous work, various villus enlarging and reducing factors present in the intestinal chyme were found to control villus size. A villus enlarging factor which appeared to reach the intestine through the duodenal papilla was presently investigated.Transplants of duodenal papilla, together with a small segment of the duodenum, were made to isolated ilea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
1
4

Year Published

1972
1972
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(82 citation statements)
references
References 5 publications
1
76
1
4
Order By: Relevance
“…In their model, a duodenal segment including the pancreatic duct was anastomosed to the ileum. They found thickening of ileal mucosa at the site receiving diverted pancreatic juice, while no changes were detected in the small intestinal mucosa proximal to the anastomotic site (Altmann 1972). In this model, however, bile was also diverted to the colon from the duodenum.…”
Section: Discussion Evaluation Of the Experimental Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In their model, a duodenal segment including the pancreatic duct was anastomosed to the ileum. They found thickening of ileal mucosa at the site receiving diverted pancreatic juice, while no changes were detected in the small intestinal mucosa proximal to the anastomotic site (Altmann 1972). In this model, however, bile was also diverted to the colon from the duodenum.…”
Section: Discussion Evaluation Of the Experimental Modelmentioning
confidence: 99%
“…Altmann investigated the effects of luminal pancreatic juice and bile on the growth of small intestinal mucosa in rats; it was reported that pancreatic juice and bile had trophic effect on the intestinal mucosa (Altmann and Leblond 1970;Altmann 1972). In their model, a duodenal segment including the pancreatic duct was anastomosed to the ileum.…”
Section: Discussion Evaluation Of the Experimental Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Pancreatobillary secretions Increased secretions associated with hyperplastic response of the intestinal mucosa. [40][41][42][43] Hormones, e.g. growth hormone Mucosal proliferation (only in rodent studies).…”
Section: Growth Hormonementioning
confidence: 99%